Comments on the holotype of Alburnus kurui Mangit & Yerli 2018 and re-description of A. carianorum Freyhof, Kaya, Bayçelebi, Geiger & Turan, 2019 (Teleostei: Leuciscidae) - Freyhof, Jörg; Kaya, Cüneyt; Bayçelebi̇, Esra; Geiger, Matthias; Turan, Davut (Zootaxa, 2019)
Article 16.4. of the International Code for Zoological Nomenclature (ICZN, 1999) requires that the fixation of name-bearing types for a new species to be explicit: “Every new specific and subspecific name published after 1999, except a new replacement name…, must be accompanied in the original publication 16.4.1. by the explicit fixation of a holotype,…..and 16.4.2. where the holotype or syntypes are extant specimens, by a statement of intent that they will be (or are) deposited in a collection and a statement indicating the name and location of that collection.” That means that for species described after 1999, the holotype must be finally deposited in a collection and it is obligatory to indicate the name of the collection and where it is located.